“Diseño de un brazo robot hidráulico de desplazamiento automático asistido por computadora” - Rucoba Reátegui, Andy Hirvyn (2014)
Currently due to the reviva! of the industry in the San Martín region, companies make many efforts to become more competitive, for which inserted into their processes, automated systems controlled by computers; however, the high costs of implementation, advisory and consultancy in process control, makes companies desist from investing in automation. Therefore, the Faculty of Engineering Systems and lnformatic of the UNSM-T, prometes research in process control, with the aim of addressing the needs of our region, supported in the robotics, study the design and construction of machines, and are able to perform tasks that makes the man. Therefore, it is necessary to design a hydraulic robot arm assisted by computer, according to the reality of companies in our region, performing an efficient design, and low cost in manufacturing. This research bases its design on technology; whereby, development projects are becoming according to our needs, based on SolidWork as a design tool, and in the LabView as a tool graphical programming, helping us to climb from design to testing and from small systems to large systems.